Application of Constructivist Approach in Madrasah Ibtidaiyah Teacher Education Learning - Teguh Handoyo; Muhlisin Muhlisin; Abdul Khobir (Lembaga Pengembangan Kinerja Dosen, 2025)
Education is the main pillar in the development of quality human resources, especially in developing countries like Indonesia. Madrasah Ibtidaiyah (MI) as a basic education institution has an important role in shaping students' character, knowledge and skills at an early age. However, the challenges faced in education in MI are often related to less innovative teaching methods, which have an impact on students' low learning motivation and academic results. The constructivist approach, which emphasizes the active role of students in the learning process, has been proven effective in improving the quality of learning. However, its application in teacher education in MI is still limited. This study aims to explore the application of the constructivist approach in teacher education in MI and its implications for learning quality. By applying this approach, it is expected that prospective teachers can develop better pedagogical skills, understand the different learning styles of students, and meet the demands of a curriculum that emphasizes 21st century skills. The research also highlights the importance of creating an inclusive learning environment where all students can actively participate. The results of the study are expected to contribute significantly to the development of education in Indonesia, particularly in the context of basic education, as well as providing insights into the integration of constructivist approaches in the teacher education curriculum at Madrasah Ibtidaiyah.